Learning Strategies for Philosophy Based on Local Wisdom in Islamic Education through the Ider Bumi Pakistaji Tradition - Khoirul Anam; Zainul Arifin; Ahmad Fadil Ilhami; Ahmad Husin (Lembaga Yasin AlSys, 2026)
Modern education in the era of globalization faces significant risks of dehumanization and identity crisis, particularly when learning is detached from local traditions, cultural values, and religious foundations. This study aims to examine local wisdom-based philosophy learning in Islamic education as an educational model that develops learners with broad global insight while maintaining commitment to local and Islamic principles. This study employed a qualitative method and was conducted in Pakistaji Village, Banyuwangi Regency, over five days. The research process included literature study, interviews, qualitative data analysis, and documentation. The findings show that philosophy learning based on local wisdom in Islamic education through the Ider Bumi Pakistaji tradition provides three main educational contributions. First, it equips students with critical thinking skills that enable them to evaluate external influences according to Islamic and local ethical values. Second, it strengthens the younger generation’s cultural roots and religious values amid globalization. Third, it balances intellectual development through philosophical reasoning with noble character through humanistic and moral values. This study concludes that integrating local wisdom into philosophy learning within Islamic education can serve as a culturally grounded and religiously informed response to the challenges of globalization. Its contribution lies in reinforcing an educational model that promotes critical awareness, cultural identity, and moral character while preparing learners to engage responsibly with global change.